The Trans-Frontal-Sinus Subcranial Approach for Removal of Large Olfactory Groove Meningiomas: Surgical Technique and Comparison to Other Approaches - Boari, Nicola; Gagliardi, Filippo; Roberti, Fabio; Barzaghi, Lina Raffaella; Caputy, Anthony J.; Mortini, Pietro (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background and Study Objective Several surgical approaches have been previously reported for the treatment of olfactory groove meningiomas (OGM).The trans-frontal-sinus subcranial approach (TFSSA) for the removal of large OGMs is described, comparing it with other reported approaches in terms of advantages and drawbacks.Material and Methods The TFSSA was performed on cadaveric specimens to illustrate the surgical technique.Results The surgical steps of the TFSSA and the related anatomical pictures are reported. The approach was adopted in a clinical setting; a case illustration is reported to demonstrate the feasibility of the described approach and to provide intraoperative pictures.Conclusion The TFSSA represents a possible route to treat large OGMs. The subcranial approach provides early devascularization of the tumor, direct tumor access from the base without traction on the frontal lobes, good overview of dissection of the optic nerves and anterior cerebral arteries, and dural reconstruction with pedicled pericranial flap.
Keywords: olfactory groove meningiomas; anterior cranial base; skull base approaches; surgical technique; anatomical study